1998
DOI: 10.1530/eje.0.1380104
|View full text |Cite
|
Sign up to set email alerts
|

Integrins in thyroid tissue: upregulation of alpha2beta1 in anaplastic thyroid carcinoma

Abstract: Objective: To evaluate the integrin pattern in the normal thyroid gland and in different pathological disorders including malignant tumors, because the aggressiveness of several malignant tumors correlates with alterations in the expression of one or more integrins. Design: We examined the expression of integrins and E-cadherin immunohistochemically in a large and well-defined sample of normal and pathological human thyroid tissue. Methods: Cryosections of 58 thyroid tissue specimens from normal tissue, thyrot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 53 publications
3
17
0
Order By: Relevance
“…Similar findings have been reported using flow cytofluorometry, where expression of integrins such as α1β1 and α6β1 was found in normal thyroid and tumor specimens, integrin α6β4 expression was found only in thyroid carcinomas and carcinoma cell lines (111). Others have confirmed neoexpression of integrin α6β4 in thyroid carcinoma tissue (112, 113) and have also found that it is expressed in anaplastic thyroid carcinoma, an aggressive and poorly differentiated malignancy (112). …”
Section: Malignancies With Strong Evidence That Integrin β4 Expressiomentioning
confidence: 85%
“…Similar findings have been reported using flow cytofluorometry, where expression of integrins such as α1β1 and α6β1 was found in normal thyroid and tumor specimens, integrin α6β4 expression was found only in thyroid carcinomas and carcinoma cell lines (111). Others have confirmed neoexpression of integrin α6β4 in thyroid carcinoma tissue (112, 113) and have also found that it is expressed in anaplastic thyroid carcinoma, an aggressive and poorly differentiated malignancy (112). …”
Section: Malignancies With Strong Evidence That Integrin β4 Expressiomentioning
confidence: 85%
“…Adhesion receptors include cadherins, integrins, selectins, and the immunoglobulin superfamily (Dahlman et al 1998). Compared with normal thyroid and differentiated cancers, ATCs have reduced cadherin 1, type 1, E-cadherin (epithelial) (Dahlman et al 1998, Husmark et al 1999) and increased integrin α2β1 subunit expression (Dahlman et al 1998).…”
Section: Functional Genomicsmentioning
confidence: 99%
“…Compared with normal thyroid and differentiated cancers, ATCs have reduced cadherin 1, type 1, E-cadherin (epithelial) (Dahlman et al 1998, Husmark et al 1999) and increased integrin α2β1 subunit expression (Dahlman et al 1998). Normal cells at high density become growth arrested at the G1 phase.…”
Section: Functional Genomicsmentioning
confidence: 99%
“…The a 2 b 1 integrin heterodimer is classically a collagen and laminin receptor limited to the basal surface when expressed by epithelia, but is present at contact sites between keratinocytes, suggesting that this integrin can also serve as an intercellular adhesion molecule and/or ligand bridging receptor (Symington et al 1993). It is noteworthy that a 2 b 1 expression is enhanced in some proliferating and migrating epithelia, including carcinomas, showing a circumferential cell staining pattern nearly identical to E-cadherin (Zutter & Santoro 1990, Dahlman et al 1998. In the present study, there was a dramatic induction of a 2 b 1 along the entire basolateral surface of LE and GE in response to progesterone.…”
Section: Progesterone Effects On Development Of Pig Gementioning
confidence: 99%